CO2 adsorption and CO2/CH4 separation using fibrous amine-containing adsorbents: isothermal, kinetic, and thermodynamic behaviours - Mohamad, Noor Ashikin (Springer, 2023)
A series of fibrous aminated adsorbents for CO2 adsorption were prepared by covalent incorporation of poly (glycidyl methacrylate) (PGMA) by graft copolymerization of GMA onto electron beam (EB) irradiated polyethylenepolypropylene (PE/PP) fibrous sheets and subsequent amination with ethylenediamine (EDA), diethylenetriamine (DETA), or tetraethylenepentamine (TEPA). The physico-chemical properties of the adsorbents were evaluated using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric (TGA), X-ray diffraction (XRD), and Brunauer–Emmett–Teller (BET) analysis. All the adsorbents displayed typic primary and secondary amine features combined with a decrease in both of crystallinity and surface area of PE/PP, and such a decrease was higher in adsorbents with longer aliphatic chain of the amine. Of all adsorbents, TEPA-containing fibres showed the highest CO2 adsorption capacity and thus was further investigated for CO2 capture from CO2/CH4 mixtures of different gas ratios under various pressures and temperatures. The selectivity of CO2 over CH4 and equilibrium isotherms, kinetics, and thermodynamics of the adsorption on the fibrous aminated adsorbent were all investigated. The Sips model was found to best fit the isotherm of CO2 adsorption suggesting the presence of a combination of monolayer and multilayer adsorptions. The adsorption kinetic data was found to best fit Elovich model reflecting chemisorption. The ?G°, ?S°, and ?H° showed positive values suggesting that the adsorption of CO2 on the present fibrous adsorbent was non-spontaneous with an increase in randomness implying that the process was endothermic. Overall, it can be suggested that PE/PP-g-PGMA/TEPA adsorbent has a strong potential for separation of CO2 from NG.